Regionalization of environmental and economic performances of rainwater harvesting systems - Ali, Shahbaz; Sang, Yan-Fang; Yang, Moyuan; Shi, Jiali; Zhang, Shouhong (Journal of hydrology. Regional studies, 2024)
Beijing Region Limited studies have yet been done on regionalization of multi-performances of rainwater harvesting systems (RHS). In this study, the daily rainfall records from 77 stations are used, and a hydro-economic model is adopted to examine regional water saving, stormwater control and economic performances of RHS by proposing a regionalization approach. Higher water saving efficiency (WSE) and reliability (R) of RHS are linked with lower water demand, larger tank size and greater rainfall conditions. Differently, higher stormwater capture efficiency (SCE) is related to higher water demand, larger tank size and lower rainfall. The WSE and R of RHS demonstrate substantial regional differences; their maximized obtainable values closely depend on water demand scenarios and range from 9% to 99%, with smaller values in western mountain area but larger values in northeast suburban and central urban areas. The maximum obtainable values of SCE range from 61% to 100%, with higher values in western mountain area, but lower values in northeast suburban and central urban areas. A 10 m3 tank size can provide the highest benefit-cost ratio of RHS across the Beijing region. The regionalization approach proposed is a useful guidance for the implementation of RHS and sustainable urban water management, and thus it has the potential for wide uses in other regions with high rainfall gradients. [Display omitted] •A regionalization approach is proposed to explore RHS’ enviro-economic efficiency.•Northeast suburban-central urban area of Beijing is favorable for RHS’ water saving.•Western mountain area of Beijing is favorable for stormwater control from RHS.•Good economic performance of RHS is observed in northeast suburban area of Beijing.